O anticlericalismo brasileiro: A Lanterna revisitada (1901-1935) - Schuck, Maria Emilia Martins Pinto (2018)
The objective of this Dissertation is to analyze Brazilian anticlericalism in the newspaper A Lanterna (1901-1935). We understand that this newspaper was the main representative of the anti-clerical movement and it was widely publicized throughout Brazil in the 20th century. This only occurred mainly due to anticlerical leagues, Masonic strongholds, Kardecist spiritists and anarchists. Brazilian anticlericalism presented specific characteristics differentiated, for example, from French anticlericalism. We started with the hypothesis that Brazilian anticlericalism in the newspaper A Lanterna was much more religious than political, because through the analysis of the discourse contained in the newspaper we were able to identify elements of attack on clerics of a moral and dogmatic order. In addition, the social space was a field of contention for other religions in the context of the transition from monarchy to the Brazilian Republic. The process of laicization that began in the Constitution of 1891 and boosted the anticlerical Brazilian movement. We can observe that until the mid-1930s the religious clash was intense, characterized by various forms of contestation of the influence of the Catholic Church in the Brazilian public space